Immunotheranostic Polymersomes Modularly Assembled from Tetrablock and Diblock Copolymers with Oxidation-Responsive Fluorescence - Du, Fanfan (Cell Mol Bioeng, 2017)
INTRODUCTION: Intracellular delivery is a key step for many applications in medicine and for investigations into cellular function. This is particularly true for immunotherapy, which often requires controlled delivery of antigen and adjuvants to the cytoplasm of immune cells. Due to the complex responses generated by the stimulation of diverse immune cell populations, it is critical to monitor which cells are targeted during treatment. To address this issue, we have engineered an immunotheranostic polymersome delivery system that fluorescently marks immune cells following intracellular delivery. METHODS: Amine functionalized poly(ethylene glycol)-bl-poly(propylene sulfide) (PEG-PPS-NH(2)) was synthesized by anionic ring opening polymerization and bridged via perylene bisimide (PBI) to form a tetrablock copolymer (PEG-PPS-PBI-PPS-PEG). Block copolymers were assembled into polymersomes by thin film hydration in phosphate buffered saline and characterized by dynamic light scattering, cryogenic electron microscopy and fluorescence spectroscopy. Polymersomes were injected subcutaneously into the backs of mice, and draining lymph nodes were extracted for flow cytometric analysis of cellular uptake and disassembly. RESULTS: Modular self-assembly of tetrablock/diblock copolymers in aqueous solutions induced π–π stacking of the PBI linker that both red-shifted and quenched the PBI fluorescence. Reactive oxygen species within the endosomes of phagocytic immune cell populations oxidized the PPS blocks, which disassembled the polymersomes for dequenching and shifting of the PBI fluorescence from 640 to 550 nm emission. Lymph node resident macrophages and dendritic cells were found to increase in 550 nm emission over the course of 3 days by flow cytometry. CONCLUSIONS: Immunotheranostic polymersomes present a versatile platform to probe the contributions of specific cell populations during the elicitation of controlled immune responses. Flanking PBI with two oxidation-sensitive hydrophobic PPS blocks enhanced π stacking and introduced a mechanism for disrupting π–π interactions to shift PBI fluorescence in response to oxidative conditions. Shifts from red (640 nm) to green (550 nm) fluorescence occurred in the presence of physiologically relevant concentrations of reactive oxygen species and could be observed within phagocytic cells both in vitro and in vivo. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12195-017-0486-7) contains supplementary material, which is available to authorized users.